1984
DOI: 10.1038/clpt.1984.105
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine: Kinetics and dynamics in healthy subjects

Abstract: Kinetics and pharmacologic effects of three formulations of nifedipine were examined in six healthy young men in a crossover design. Each subject received intravenous nifedipine, 0.015 mg/kg body weight, 20 mg in a capsule, and 20 mg in a slow-release tablet. Changes in heart rate (HR), blood pressure, heart dimensions, and plasma norepinephrine levels (PNE) were examined serially. Plasma concentrations of nifedipine (Cp) and urinary metabolite concentrations were measured by liquid chromatography. After intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
71
0
2

Year Published

1986
1986
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(86 citation statements)
references
References 0 publications
10
71
0
2
Order By: Relevance
“…The present study demonstrated that the fractions of dose absorbed (F) in both forms are rather low (0.18-0.63). These values of pharmacokinetic parameters are essentially similar to those reported previously (Brennan et al 1983;Raemsch and Sommer 1983;Taburet et al 1983;Kleinbloesem et al 1984). The values of systemic availability of nifedipine suggest that the absorption is incomplete or this substance is subjected to the first pass effect, or both.…”
Section: Discussionsupporting
confidence: 78%
“…The present study demonstrated that the fractions of dose absorbed (F) in both forms are rather low (0.18-0.63). These values of pharmacokinetic parameters are essentially similar to those reported previously (Brennan et al 1983;Raemsch and Sommer 1983;Taburet et al 1983;Kleinbloesem et al 1984). The values of systemic availability of nifedipine suggest that the absorption is incomplete or this substance is subjected to the first pass effect, or both.…”
Section: Discussionsupporting
confidence: 78%
“…Nifedipine usually shows no marked antihypertensive eŠect in normal individuals, because the diastaltic sympathicotonia through pressoreceptor with decreases of peripheral arterial resistance induces the increases of heart rate, and prevents blood pressure decreases. 20) However, there have been reports [21][22][23][24][25][26][27][28] that nifedipine signiˆcantly reduced the blood pressure by oral and sublingual administration and that the serum nifedipine concentration was correlated with the antihypertensive eŠect in normal individuals. In our study, also, the serum concentration was correlated with blood pressure, especially DBP, by each administration method.…”
Section: Discussionmentioning
confidence: 99%
“…However, this proposed mechanism does not explain the increased plasma level of nifedipine associated with concomitant administration of diltiazem. Such a mechanism would also raise the diltiazem plasma concentration, since nifedipine is a stronger vasodilator than diltiazem and diltiazem undergoes more extensive first-pass metabolism than does nifedipine (their bioavailabilities are 42%33 and 55% to 63%, 34 In summary, the results of this study indicate that, in patients with effort angina, exercise tolerance is increased by the concomitant administration of diltiazem and nifedipine. This effect appears to be partly a consequence of an increase in the nifedipine plasma concentration as an expression of drug interaction.…”
Section: Resultsmentioning
confidence: 59%